ANALISIS NILAI-NILAI KONSELOR MULTIKULTURAL DALAM BUDAYA MITONI - Intan Revlina (STKIP PGRI SUMENEP, 2023)
Mitoni culture is one form of cultural acculturation in Java. Mitoni is an acculturation of Islamic culture with Kejawen culture, mitoni has a series of events: 1) spraying setaman flowers, 2) husband inserting free-range chicken eggs into the cloth of pregnant women, 3) changing clothes seven times, 4) Angrem ceremony, 5) ceremony dodol rujak, 6) break two ivory coconuts. The values ??of multicultural counselors contained in the mitoniritual are 1) awareness of personal values, 2) awareness of having their own values ??that must be upheld; 3) accept different values ??from clients and learn them; 4) knowing the influence of ethnicity and concern for the environment; 5) respond to differences that have the potential to hinder the counseling process; 6) does not encourage clients to be able to understand the culture and values ??of the counselor.